Ranking of Websites of State Universities in Tamil Nadu using WISER and PRIMOEX: An Analytical Study - Dhanavandan, S.; Varadharajalu, J. (International Journal of Knowledge Content Development & Technology, 2019)
This Study examines and explores through a web metric ranking analysis of the websites of 22 state universities in Tamil Nadu. It discussed the domain systems of the websites; WISER Web ranking for the year 2016 and 2017. Similarly the researchers manipulated a new ranking tools for ranking the websites of State universities of Tamil Nadu, According to WISER ranking, Anna University is ranked first with 2469.4 WISER value followed by Tamil Nadu Agricultural University which is ranked second with 4031.4 WISER value. University of Madras is ranked third with 4333.8 WISER values in the year 2017. But . But when we used the PRIMOEX ranking, Anna University is ranked first with 3653.3 PRIMOEX value followed by Tamil Nadu Agricultural University which is ranked second with 4090.6 PRIMOEX value. Madurai Kamaraj University is ranked third with 4136.1 PRIMOEX values. Alagappa University is ranked fourth with 4956.1 PRIMOEX value and Alagappa University with 6001.9 PRIMOEX value is ranked fifth. It found that PRIMOEX good tool to measure the ranking of websites of state universities of Tamil Nadu. URL: http://ijkcdt.net/xml/21158/21158.pdf